Magnetic and magnetocaloric properties of Fe2AlB2 synthesized by single-step reactive hot pressing. (November 2020) - Bennett, Steven P.; Kota, Sankalp; ElBidweihy, Hatem; Parker, Joseph F.; Hanner, Luke A.; Finkel, Peter; Barsoum, Michel W.
Abstract: A single-step, reactive hot-pressing technique was used to synthesize dense, polycrystalline samples of the nanolaminated MAB phase, Fe2 AlB2 . The process yielded nearly single-phase stoichiometric Fe2 AlB2 materials containing only Al2 O3 as the impurity phase in a fraction of the synthesis time typically required for the more commonly used arc-melting methods. To determine crystalline, magnetic, and stoichiometric properties, samples were analyzed by X-ray diffraction, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy, and temperature-dependent vibrating sample magnetometry. The results of both magnetic techniques show magnetic and magnetocaloric properties similar to those obtained in the literature by other methods such as multi-day arc melting and annealing. Graphical abstract: Image, graphical abstract